2010
DOI: 10.1684/epd.2010.0327
|View full text |Cite
|
Sign up to set email alerts
|

Type I focal cortical dysplasia: surgical outcome is related to histopathology

Abstract: Pre-surgical and post-surgical data were examined and compared from 215 consecutive patients undergoing surgery for intractable epilepsy. Patients were selected on the basis of a proven histopathological diagnosis of type I focal cortical dysplasia (FCD I), alone or associated with other lesions. The patients were divided into five sub-groups: i) 66 with isolated FCD I, ii) 76 with FCD I and hippocampal sclerosis, iii) 49 with FCD I and tumours, iv) 16 with FCD I and other malformations of cortical development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
74
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 54 publications
9
74
2
6
Order By: Relevance
“…Our finding is in contrast to reports in the recent literature, including patients with HS and FCD, where the outcome was reported to be similar to isolated HS and better than FCD I (Tassi et al, 2009(Tassi et al, , 2010Thom et al, 2009). There were methodological differences in cohort selection between our study and both Tassi et al (2009Tassi et al ( , 2010 and Thom et al (2009), which may explain these disparate findings. Thom et al (2009) excluded all patients with associated FCD, aside from a specific subgroup with temporal lobe sclerosis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our finding is in contrast to reports in the recent literature, including patients with HS and FCD, where the outcome was reported to be similar to isolated HS and better than FCD I (Tassi et al, 2009(Tassi et al, , 2010Thom et al, 2009). There were methodological differences in cohort selection between our study and both Tassi et al (2009Tassi et al ( , 2010 and Thom et al (2009), which may explain these disparate findings. Thom et al (2009) excluded all patients with associated FCD, aside from a specific subgroup with temporal lobe sclerosis.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have shown its clinical characteristics reflected its primary pathology (e.g. hippocampal sclerosis (HS) in FCD IIIA) rather than the associated dysplasia (Tassi et al, 2009(Tassi et al, , 2010. We aimed to determine the frequency of FCD type IIIA pathology in a cohort of temporal lobe epilepsy (TLE) surgical patients and whether FCD IIIA has a distinct electroclinical phenotype with identifying imaging features and prognostic implications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with FCDs generally present high frequencies of seizures (Tassi et al 2002(Tassi et al , 2010(Tassi et al , 2012. FCDs were first described by Taylor in details, which showed a strange histopathology including abnormal cortical layering and large bizarre neurons such as dysmorphic neurons (DNs) and balloon cells (BCs) (Taylor et al 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the changes seen in this setting are acquired, that is, the hippocampal sclerosis lesion and focal cortical dysplasia result from reorganization (dysplasia) or injury resulting in hippocampal sclerosis, or these cases represent a distinct developmental abnormality whereby the hippocampal sclerosis develops secondary to chronic epilepsy resulting from the focal cortical dysplasia lesion is uncertain. The lack of clinical differences and postsurgical outcomes between hippocampal sclerosis and hippocampal sclerosis with focal cortical dysplasia patients would argue for a common etiology [28,29].…”
Section: Discussionmentioning
confidence: 99%